Analisis Semiotika: Makna Denotatif dan Konotatif dalam Film Spongebob Squarepants Episode 9 “Uh, Bulu Babi” Season 9 (Dubbing Bahasa Arab) - Muhammad Yazid Yaskur (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
This research aims to analyze the semiotic meaning of denotative and connotative in the use of Arabic in the episode